2014
DOI: 10.1589/jpts.26.483
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Usefulness of Sit to Stand Training in Self-directed Treatment of Stroke Patients

Abstract: [Purpose] This study sought to determine the usefulness of sit to stand training in self-directed treatment of stroke patients. It examined the effect that sit to stand training has on balance and functional movement depending on the form of support surfaces. [Subjects and Methods] Thirty stroke patients were randomly sampled and divided into an unstable support surface group (15) and stable support surface group (15). In order to identify the effect depending on the form of support surfaces, 15 minutes of sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Meanwhile, the position of the asymmetric feet while standing up from a sitting position improves the static and dynamic postural balance in patients with stroke (17). In addition, the use of the step model, motion limiting strategies, repetition of sitting motion, repetitive task-oriented practice with sensory input changes, exercise on unstable surfaces, and the use of a cane and weight-bearing exercises along with biofeedback have been reported to improve the STS task in this group of patients (18,20,30,32,(35)(36)(37)(38). Interventions or training focusing on the sit-to-stand task improves the time taken to sit-to-stand and the lateral symmetry (weight distribution between the legs) during the sit-to-stand task (6).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Meanwhile, the position of the asymmetric feet while standing up from a sitting position improves the static and dynamic postural balance in patients with stroke (17). In addition, the use of the step model, motion limiting strategies, repetition of sitting motion, repetitive task-oriented practice with sensory input changes, exercise on unstable surfaces, and the use of a cane and weight-bearing exercises along with biofeedback have been reported to improve the STS task in this group of patients (18,20,30,32,(35)(36)(37)(38). Interventions or training focusing on the sit-to-stand task improves the time taken to sit-to-stand and the lateral symmetry (weight distribution between the legs) during the sit-to-stand task (6).…”
Section: Discussionmentioning
confidence: 97%
“…Stand-up exercises were not effective on supportable levels than on the unstable positions; however, it can be a simple and stable exercise with less risk of injury during training and practice. Therefore, it can be used as a useful exercise performed alone by the patient outside the treatment room (32). Practicing sit-up for stroke patients is useful because of its effect on dynamic stability and extensor muscle strength (33).…”
Section: Type Of Exercisementioning
confidence: 99%
“…This study examined the differences in erector spinae and gluteus maximus muscle activities during STS with different foot placements. Mun et al examined the effect of different support surfaces on the functional movement ability of stroke patients during STS 12 ) . Stephen et al 8 ) reported that after STS and maintaining stance, the erector spinae and gluteus maximus muscles were activated continuously, and that during STS, when the COM travels forward and then upward, maximal erector spinae muscle activation was seen.…”
Section: Discussionmentioning
confidence: 99%
“…The ability to stand up and sit down is crucial to perform such basic activities of daily living (Lindermann et al., ; Slaughter et al, ). The sit‐to‐stand motion refers to the process of shifting the centre of mass from a sitting position to a standing position (Mun et al., ). Difficulties in performing this movement are seen in older people with physical limitations, cognitive decline or dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Difficulties in performing this movement are seen in older people with physical limitations, cognitive decline or dementia. For frail institutionalised older people, repeated sit‐to‐stands can be sufficient to reduce functional limitations and improve lower limb strength (Dolecka, Ownsworth, & Kuys, ; Mun et al., ; Slaughter et al, ). In one study, residents with dementia who were prompted to complete the sit‐to‐stand activity over six months were compared with a control group of similar residents who did not complete the sit‐to‐stands (Slaughter et al, ).…”
Section: Introductionmentioning
confidence: 99%